Cognitive Biases Influencing Accounting Estimates and Audit Evaluations (gjstudies, 2025)
This research investigates the underexplored intersection of cognitive psychologyand accounting practice, specifically examining how systematic cognitive biases influence the formation of accounting estimates and subsequent audit evaluations. Whiletraditional accounting research has focused on technical standards and economic incentives, this study adopts a novel interdisciplinary approach, applying frameworksfrom behavioral economics and cognitive science to professional judgment in financial reporting. We identify and analyze five specific biases—anchoring, confirmationbias, overconfidence, availability heuristic, and representativeness heuristic—that persistently affect accountants and auditors despite professional training and standards.Through a mixed-methodology design incorporating controlled experiments with practicing professionals and archival analysis of restatements, we demonstrate that thesebiases significantly alter point estimates, increase estimation ranges, and reduce theeffectiveness of audit challenge. A key finding is the ’professional shield’ paradox:expertise and experience, while reducing some simple errors, can entrench certain biases, particularly overconfidence and confirmation bias, making them more resistant tostandard auditing procedures. The study proposes and tests a novel debiasing intervention framework, the ’Cognitive Checkpoint Protocol,’ which integrates structuredreflection and counterfactual reasoning into existing audit workflows. Results indicatea statistically significant reduction in bias-induced estimation errors when the protocolis applied. This research contributes original insights by moving beyond a normativemodel of rational judgment, providing empirical evidence of predictable irrationalityin accounting, and offering a practical, theory-informed tool to enhance the quality offinancial reporting and audit assurance.